PENDIDIKAN PANCASILA, EKSISTENSINYA BAGI MAHASISWA - August Hadiwijono (Jurnal Cakrawala Hukum, 2016)
This study attempts to analyze the meaning of Pancasila for students and went to analyze Pancasila’s way on campus. The research is normative research. Development and education of Pancasila need to be done by a college in order to preserve Pancasila values and planting positive values, contained in it for the young generation especially students the student who have important and vital. In addition to Pancasila as an ideology and personality of the country. Pancasila as a view of life nations must be from early introduced and taught to communities Indonesia including college. As forming the intellectual ethical lordship and humanity. The Pancasila personality must be personality the youth particularly university students who became generation education. Through education of Pancasila, students will be human first, before entering the lecture which learned. As a citizen of Indonesia who excels in knowledge mastery, but not lost their identity and not drawn from the root culture her people and his faith. In addition, it can form personally good in social norms and had good in order to become very good citizens for themselves, others and this person in daily life. I have values Pancasila in students we can do it in on several, that is an education channel and the organization and message objectively and subjectively. If the values of Pancasila embedded with both in each individual student will be created Pancasila student who understands norms. Pancasila implementation in life on campus was very important it is for the sake of advance college to campus can produce graduates Pancasila students cannot be built by the people of Indonesia.